Research on thermohydraulic performance of the petal-type vortex generator inserted tube heat exchanger - Liu Jie; Qian Zuoqin; Yin Yemao; Wang Chao (Case Studies in Thermal Engineering)
The petal-type vortex generator inserted tube was proposed in this paper to explore higher heat transfer performance. The k-ω model was selected and a good agreement can be obtained. Basically, the influences of the interval distance t, the angle α and the pitch P were meticulously examined within a Reynolds number spectrum ranging from 5000 to 15,000. The analysis of the internal flow dynamics revealed that the petal-type vortex generator effectively transformed the longitudinal velocity of the fluid into radial velocity, leading to the formation of vortices within the tube. The petal-shaped vortex generators led a portion of the fluid toward the tube surface, facilitating boundary layer weakening and redevelopment near the wall, while also allowing another portion of the fluid to pass through the slits, which enhanced the generation of vortices and significantly improved heat transfer performance. The numerical results indicated that the tube equipped with petal-type vortex generator insert achieved a 196–347 % increase in the Nusselt number (Nu) and a 244–1149 % increase in the friction factor (f), relative to a smooth tube. The maximum performance evaluation criterion (PEC) obtained in this study reached 2.01.